Social Support And Gender As Predictors Of Readiness To Combat Crime Among Police Officers In Osun State Command, Nigeria - Ayegun, Olusola Abayomi; Ayinde, Adeboye Titus (Advances in Social Sciences Research Journal, 2018)
Police effectiveness in crime combat may not necessarily depend on how well they are remunerated or the quantity of equipment made available to them, but the quality of cooperation receives from the members of the public and their sexual orientation may also lend credence. Therefore, this study examined the extent to which social support and gender predict readiness to combat crime among police officers. This was done with a view to identifying psychosocial factors that predict readiness to combat crime among police officers in Osun State Command. The study used primary data embedded in descriptive survey design. Multistage sampling technique was adopted in determining and obtaining data from the sample population. Three police area commands namely Osogbo, Ile-Ife and Ilesa were purposively selected for the study. The sample consisted 258 police officers who were selected using the stratified random technique with different units of Command as a basis of stratification. Two instruments: Multidimensional Scale of Perceived Social Support (MSPSS) and Readiness to Combat Crime Scale (RCCS). Data collected were analysed using both descriptive (percentage count) and inferential statistics (linear regression and t-test). The results showed that social support significantly predicted readiness to combat crime among police officers in Osun State Command [F (1, 226) = 17.538; p < 0.05]. However, there was no significant gender difference in readiness to combat crime among police officer in Osun State Command [t (224) = 0.186; p > 0.05]. The study concluded that social support successfully predicted readiness to combat crime, while gender had no influence on readiness to combat crime among police officers in Osun State Command.